(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the intricate landscape of security concerns and data privacy issues surrounding digital transactions within the unorganized retail sector. As digital payment methods proliferate, unorganized retailers grapple with safeguarding sensitive customer information and ensuring transactional security. Through an exhaustive review of literature and empirical analysis, this study investigates security threats, vulnerabilities, and regulatory compliance requirements pertinent to unorganized retailers engaging in digital transactions. Furthermore, the paper examines how these security concerns and data privacy issues affect consumer trust and perception of digital transactions in the unorganized retail sector. Real-world examples and case studies underscore the tangible consequences for businesses and consumers, emphasizing the urgent need for robust security measures and proactive risk mitigation strategies. Drawing insights from industry experts and technological innovators, this paper explores emerging security technologies and best practices for enhancing transactional security and protecting customer data in unorganized retail environments. Additionally, it identifies key challenges and barriers faced by unorganized retailers in addressing these security concerns, including resource constraints and technological literacy gaps. In conclusion, the paper provides practical recommendations and strategies for unorganized retailers to bolster security and data privacy in digital transactions. These recommendations encompass collaborative industry efforts, investment in cybersecurity training, and advocacy for stronger regulatory frameworks. By addressing these security challenges proactively, unorganized retailers can foster consumer trust, mitigate risk, and unlock the full potential of digital transactions in the cashless economy.